TELEMETRY DATA MANAGEMENT: A GIS‐BASED APPROACH - Timothy S. Wynn; Eric F. Songer; George A. Hurst (Wildlife Society Bulletin)
Abstract: We developed standard procedures for storing and managing telemetry data on microcomputers to facilitate analysis. Raw location and descriptive data for several wild turkey (Meleagris gallopavo) research projects were entered into microcomputers in a standard file format used by several commercially available database management programs. Computer programs were developed to allow easy transfer of these data between a standard database format and a standard geographic information system (GIS) data exchange format. Researchers analyzed the same data set in both tabular and visually geographic form, enhancing relationships that might otherwise take longer to recognize. Standard commercial software formats minimized the time required to exchange data among analysis programs, allowing the use of programs that suited researcher's individual needs and means.